Adverse gastrointestinal effects of over-the-counter non-steroidal anti-inflammatory drugs: a cost study in two Gauteng Public Hospital - Govender, Theshni (My University, 2017)
Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most commonly used analgesics worldwide. NSAIDs are increasingly available as an expanding range of over the counter (OTC) and prescription formulations. Straube et al, in a systematic review, report the mortality rate of individuals with UGIT bleeding/perforation using chronic oral NSAIDs is 1 in 5 due to gastrointestinal complications. The economic implications to a challenged, South African public healthcare system of treating serious, potentially preventable upper gastrointestinal complications attributed to the consumption of OTC NSAIDs does not appear to have been quantified. A prospective observational study was conducted at Chris Hani Baragwanath Academic Hospital and Charlotte Maxeke Johannesburg Academic Hospital over six months. Patients admitted to the surgical service with signs and symptoms of upper gastrointestinal bleeding were asked to complete a questionnaire-based survey. The cost to treat each patient was calculated. Over the study period, 321 patients were admitted with upper gastrointestinal tract (UGIT) bleeding. The cost to treat patients included in the study sample (n=253) was R 10 463 668. Patients using NSAIDs (n=215) consumed 88% (R 9 194 698) of the expenditure, seven times more than the cost of treating patients who did not use NSAIDs (n=38; p = 0.043). Of the patients who used NSAIDS, 183 had purchased over the counter NSAIDs and consume 73% of the total expenditure. The average cost to treat a patient with UGIT complications secondary to OTC vs. Prescription NSAIDs was not statistically significant. Due the higher number of viii patients who used OTC NSAIDs the cost incurred to treat these patients was five fold more than to treat the patients taking prescription only NSAIDs. We recommend strict enforcement of existing regulations governing the sale and marketing of OTC NSAIDs and intensive consumer education of their adverse effects, which may decrease the substantial financial cost to the public health system and morbidity to the South African population at risk.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine. Johannesburg 2017.
Keywords: Upper Gastrointestinal Tract; Anti-Inflammatory Agents, Non-Steroidal; Nonprescription Drugs (OTC)